Consensus‐Based Technical Recommendations for Clinical Translation of Renal Phase Contrast MRI. Issue 2 (2nd November 2020) - de Boer, Anneloes; Villa, Giulia; Bane, Octavia; Bock, Michael; Cox, Eleanor F.; Dekkers, Ilona A.; Eckerbom, Per; Fernández‐Seara, Maria A.; Francis, Susan T.; Haddock, Bryan; Hall, Michael E.; Hall Barrientos, Pauline; et al.
Abstract : Background: Phase‐contrast (PC) MRI is a feasible and valid noninvasive technique to measure renal artery blood flow, showing potential to support diagnosis and monitoring of renal diseases. However, the variability in measured renal blood flow values across studies is large, most likely due to differences in PC‐MRI acquisition and processing. Standardized acquisition and processing protocols are therefore needed to minimize this variability and maximize the potential of renal PC‐MRI as a clinically useful tool. Purpose: To build technical recommendations for the acquisition, processing, and analysis of renal 2D PC‐MRI data in human subjects to promote standardization of renal blood flow measurements and facilitate the comparability of results across scanners and in multicenter clinical studies. Study Type: Systematic consensus process using a modified Delphi method. Population: Not applicable. Sequence Field/Strength: Renal fast gradient echo‐based 2D PC‐MRI. Assessment: An international panel of 27 experts from Europe, the USA, Australia, and Japan with 6 (interquartile range 4–10) years of experience in 2D PC‐MRI formulated consensus statements on renal 2D PC‐MRI in two rounds of surveys. Starting from a recently published systematic review article, literature‐based and data‐driven statements regarding patient preparation, hardware, acquisition protocol, analysis steps, and data reporting were formulated. Statistical Tests: Consensus was defined as ≥75% unanimity in response, and a clear preference was defined as 60–74% agreement among the experts. Results: Among 60 statements, 57 (95%) achieved consensus after the second‐round survey, while the remaining three showed a clear preference. Consensus statements resulted in specific recommendations for subject preparation, 2D renal PC‐MRI data acquisition, processing, and reporting. Data Conclusion: These recommendations might promote a widespread adoption of renal PC‐MRI, and may help foster the set‐up of multicenter studies aimed at defining reference values and building larger and more definitive evidence, and will facilitate clinical translation of PC‐MRI. Level of Evidence: 1 Technical Efficacy Stage: 1